2005
DOI: 10.1097/01.hp.0000146612.69488.9c
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance and Fluorescence in Situ Hybridization-Based Investigations of Individual Doses for Persons Living at Metlino in the Upper Reaches of the Techa River

Abstract: Waterborne releases to the Techa River from the Mayak Production Association in Russia during 1949-1956 resulted in significant doses to persons living downstream; the most contaminated village was Metlino, about 7 km from the site of release. Internal and external doses have been estimated for these residents using the Techa River Dosimetry System-2000 (TRDS-2000); the primary purpose is to support epidemiological studies of the members of the Extended Techa River Cohort. Efforts to validate the calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…After data on the exposure were disclosed to the scientific community, it was suggested that EPR dosimetry using tooth enamel could be suitable for reconstruction of doses in this cohort (Romanyukha et al, 1996a(Romanyukha et al, , 1996b. It is expected that validation of external doses measured in human tissues (e.g., by EPR dosimetry using tooth enamel and cytogenetic methods in blood samples) combined with results of experimental dose measurement in environmental samples (e.g., by thermoluminescence in bricks) would improve the assessment of the computed doses (Degteva et al, , 2005(Degteva et al, , 2006Jacob et al, 2003;Balonov et al, 2006). Studies are still in progress.…”
Section: Residents Of the Techa River Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…After data on the exposure were disclosed to the scientific community, it was suggested that EPR dosimetry using tooth enamel could be suitable for reconstruction of doses in this cohort (Romanyukha et al, 1996a(Romanyukha et al, , 1996b. It is expected that validation of external doses measured in human tissues (e.g., by EPR dosimetry using tooth enamel and cytogenetic methods in blood samples) combined with results of experimental dose measurement in environmental samples (e.g., by thermoluminescence in bricks) would improve the assessment of the computed doses (Degteva et al, , 2005(Degteva et al, , 2006Jacob et al, 2003;Balonov et al, 2006). Studies are still in progress.…”
Section: Residents Of the Techa River Regionmentioning
confidence: 99%
“…However, we are aware of only one group (Chumak et al, 1999) that used the additive dose method in measurements of tooth samples of large groups of population; other groups prefer to use universal calibration curves (Nakamura et al, 1998a;Ivannikov et al, 2004a;Wieser et al, 2006b;Degteva et al, 2005, to mention a few).…”
Section: Advantages and Disadvantages Of "The Calibration Curve" And mentioning
confidence: 99%
See 1 more Smart Citation
“…EPR tooth dosimetry research started to grow rapidly after the Chernobyl accident in 1986 (Aldrich and Pass, 1988, Shimano et al, 1989and Ikeya and Ishii, 1989, which resulted in maturation of the EPR technique with tooth enamel. The technique has been verified through several intercomparisons (Chumak et al, 1996, Wieser et al, 2000a and was applied for dose reconstruction of A-bomb victims (Ikeya et al, 1984 andNakamura et al, 1998), Chernobyl liquidators , the population in territories contaminated due to the Chernobyl accident (Skvortzov et al, 1995, Skvortzov et al, 2000, Ivannikov et al, 1997, Ivannikov et al, 2004band Ivannikov et al, 2014, residents near the Semipalatinsk Nuclear Test Site (SNTS, Kazakhstan) , Zhumadilov et al, 2009, Zhumadilov et al, 2011a, Zhumadilov et al, 2011b, Zhumadilov et al, 2013Ivannikov et al, 2002, Pivovarov et al, 2002and Sholom et al, 2007a, and the inhabitants of the Techa River basin affected by the operation of the Mayak Production Association , Degteva et al, 2005, Degteva et al, 2015.…”
Section: Retrospective Dosimetrymentioning
confidence: 99%
“…It is a method used for validating dosimetry in epidemiological studies (Degteva et al, 2005;Wieser et al, 2006a) and post-accident scenarios . A significant number of laboratories around the world have set up this method by developing specific protocols of measurement.…”
Section: Introductionmentioning
confidence: 99%